Equações Diferencias Parciais -uma Abordagem Introdutório a Modelagem de Pontos Quânticos - Silva, Edeilson Cruz da (2023)
This paper enphasizes on possible applications of Partidal Differential Equations (PDEs) in physics, whith focus on mathematical techiniques as methods of separation of variables as well as the use of spherical and cylindrical harmonics as fundamentais tools over those approaches. In addition, we will justify the study of these methods, considering their relevance in modeling such exquisite and complex systems